2006
DOI: 10.1007/s10561-006-9000-5
|View full text |Cite
|
Sign up to set email alerts
|

Functional properties of fresh and cryopreserved carotid and femoral arteries, and of venous and synthetic grafts: comparison with arteries from normotensive and hypertensive patients

Abstract: The ideal arterial graft must share identical functional properties with the host artery. Surgical reconstruction of the common carotid artery (CA) is performed in several clinical situations, using expanded polytetrafluoroethylene prosthesis (ePTFE) or saphenous vein (SV) grafts. At date there is interest in obtaining an arterial graft that improves the results of that nowadays available. The use of a fresh or cryopreserved/defrosted artery appears as an interesting alternative. However, if the fresh and cryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 34 publications
(52 reference statements)
0
20
0
Order By: Relevance
“…The longitudinal TS values of our TLVGs (0.47±0.02 MPa) were higher compared to those (0.24±0.10 MPa) of triple layered scaffolds prepared by Koens et al (9). Furthermore, the Young's modulus of our TLVGs (1.8 MPa) was comparable to that of porcine coronary artery (1 MPa) (31), rabbit aorta (1.25 MPa) (32) and human saphenous or femoral vein (1.50 MPa) (33). Scaffold strength provides the firmness to resist cell contraction forces, whereas elasticity enables better communication between cells, facilitating parallel organization (27,37,38) and ensuring the maintenance of a tubular shape in our constructs.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…The longitudinal TS values of our TLVGs (0.47±0.02 MPa) were higher compared to those (0.24±0.10 MPa) of triple layered scaffolds prepared by Koens et al (9). Furthermore, the Young's modulus of our TLVGs (1.8 MPa) was comparable to that of porcine coronary artery (1 MPa) (31), rabbit aorta (1.25 MPa) (32) and human saphenous or femoral vein (1.50 MPa) (33). Scaffold strength provides the firmness to resist cell contraction forces, whereas elasticity enables better communication between cells, facilitating parallel organization (27,37,38) and ensuring the maintenance of a tubular shape in our constructs.…”
Section: Discussionmentioning
confidence: 50%
“…The layer deposition procedure allowed us to obtain smalldiameter TLVGs of different sizes using DAM from bovine aorta containing ECM components, which are naturally present in blood vessels. Our findings show that these novel tailor-made vascular grafts present mechanical properties comparable to those of native vessels (31)(32)(33). Furthermore, the lyophilization process makes them easy to store.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…On the other hand, the biomechanical studies conducted on the venous wall correspond mainly to the field of strength of materials and are nonrealistic, static, and carried out in nonphysiological conditions [5]. Furthermore, most works do not refer to the viscous response of the wall [6]. In this context, the purpose of this work includes the characterization of the venous functional biomechanical behavior, through the analysis of the dynamic biomechanical response of the venous wall, under a hemodynamic setting that resembles physiological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the exact pre-procedural evaluation of the distal ICA diameter is difficult. Although Santana et al reported the elastic modulus of the carotid artery as 707 KPa [15], there may be individual differences with respect to the ICA. The ICA with a lower elastic modulus may be easily expanded by oversized stents and reduce the chronic expansile force promoting greater neointimal hyperplasia.…”
Section: Discussionmentioning
confidence: 98%